2022
DOI: 10.1002/rcs.2410
|View full text |Cite
|
Sign up to set email alerts
|

Safety enhanced surgical robot for flexible ureteroscopy based on force feedback

Abstract: Background: Although some robotic systems have been developed to improve conventional flexible ureteroscopy (FURS), a widely used intervention in urology, these robots rarely have a comprehensive force feedback function which is important for master-slave controlled surgical robots.Methods: Here, we design and fabricate a novel FURS robot with a comprehensive force feedback function. Moreover, to realize better force feedback, a neural network-based method is also demonstrated to estimate the interactive force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Finally, the ILY and other robots lack tactile feedback. However, the technology is being developed to incorporate force feedback into robotic fURS in the future [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the ILY and other robots lack tactile feedback. However, the technology is being developed to incorporate force feedback into robotic fURS in the future [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using a neural network-based approach to estimate the interaction force between the flexible ureteral scope and the environment, the operator can accurately perceive obstacles when the interacting axial force or torque exceeds 1.2 N or 15.6 mN·m, respectively, during the robot’s teleoperation of the flexible ureteral scope. This force feedback greatly improves the accuracy of the operator’s obstacle perception and is expected to improve the safety of robotic-assisted FURS 79 .…”
Section: New Equipment New Technologymentioning
confidence: 99%
“…In 2022, Shu et al [ 5 ] demonstrated their robotic RIRS system, which is based on force feedback with a neural network-based method. In their prototype system, the operator can accurately feel the obstruction if the interactive axial force or torque exceeds 1.2 N or 15.6 mN·m, respectively.…”
Section: Recent Publications On Robotic Rirs and New Prototypesmentioning
confidence: 99%
“…Soon, most robotic RIRS systems should have force feedback using haptic sense. Thus, the study by Shu et al [ 5 ] marked the beginning of this latest technology for enhancing the safety of robotic endoluminal surgery.…”
Section: Recent Publications On Robotic Rirs and New Prototypesmentioning
confidence: 99%